2016
DOI: 10.1021/acs.orglett.6b01678
|View full text |Cite
|
Sign up to set email alerts
|

Melonoside A: An ω-Glycosylated Fatty Acid Amide from the Far Eastern Marine Sponge Melonanchora kobjakovae

Abstract: Melonoside A (1), the first representative of a new class of ω-glycosylated fatty acid amides, was isolated from the Far Eastern marine sponge Melonanchora kobjakovae. The structure of 1, including absolute configuration, was established using detailed analysis of 1D and 2D NMR, CD, and mass spectra as well as chemical transformations. Compound 1 induces autophagy of human cisplatin-resistant germinal tumor cells NCCIT-R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 27 publications
6
28
0
Order By: Relevance
“…A number of new glyceride (788 and 789) and ceramide (790-793) lipids have been reported from species of Theonella and Erylus, 394,395 while branched fatty acids (794 and 795), polyoxygenated fatty acid amides (796 and 797) and N-acyldopamine glycosides 798-801 were sourced from Asteropus, Melonanchora, Myxilla and Theonella sponges. [396][397][398][399] Unusually, only one new polyacetylene 802 was reported in 2016, from Halichondria panicea. 400 Examination of the two-sponge association between Xestospongia deweerdtae and Plakortis halichondrioides, in addition to P. zyggompha, resulted in the isolation of 6-epi-7,8dihydroplakortide K 803, plakortide AA 804, and three chemically unstable plakinic acids N-P 805-807.…”
Section: Spongesmentioning
confidence: 99%
“…A number of new glyceride (788 and 789) and ceramide (790-793) lipids have been reported from species of Theonella and Erylus, 394,395 while branched fatty acids (794 and 795), polyoxygenated fatty acid amides (796 and 797) and N-acyldopamine glycosides 798-801 were sourced from Asteropus, Melonanchora, Myxilla and Theonella sponges. [396][397][398][399] Unusually, only one new polyacetylene 802 was reported in 2016, from Halichondria panicea. 400 Examination of the two-sponge association between Xestospongia deweerdtae and Plakortis halichondrioides, in addition to P. zyggompha, resulted in the isolation of 6-epi-7,8dihydroplakortide K 803, plakortide AA 804, and three chemically unstable plakinic acids N-P 805-807.…”
Section: Spongesmentioning
confidence: 99%
“…Ozonolysis is easily adapted to the microscale level, particularly when used along with mass spectrometry. For example, this reaction in MeOH without following treatment leads to hydroperoxides, which are stable enough to be used in mass spectrometric analyses as shown for the studies on melonoside A ( 115 ) from the sponge Melonanchora kobjakovae . Application gave derivative 116 with mass spectrometry confirming the 21(22) position of one of the double bonds, while the other was located at the 5(6)-position on the basis of NMR experiments.…”
Section: Ozonolysismentioning
confidence: 99%
“…However, it should be noted that earlier studies have reported the autophagy inducing activity of EPA in several human cancer and non-cancer cells, which was, in the majority of cases, reported to be cytoprotective [ 132 , 133 , 134 , 135 ]. In 2016, Guzii et al announced the isolation of an ω-glycosylated fatty acid amide melonoside A from the marine sponge Melonanchora kobjakovae [ 136 ]. The authors reported the induction of autophagy in human cisplatin-resistant germinal tumor (GCT) NCCIT-R cells.…”
Section: Marine Compounds With a Non-validated Autophagy-modulatormentioning
confidence: 99%
“…The authors reported the induction of autophagy in human cisplatin-resistant germinal tumor (GCT) NCCIT-R cells. This conclusion was made based on the observed downregulation of LC3B-II and SQSTM1/p62 proteins in the treated cells [ 136 ], which often reflects the acceleration of the autophagosome turnover, i.e., increased autophagy [ 7 , 8 , 30 , 31 ]. However, further experiments are expected to clarify the effect of melonoside A on autophagy in mammalian cells.…”
Section: Marine Compounds With a Non-validated Autophagy-modulatormentioning
confidence: 99%